A single case study: Excision of Medojagranthi (PedunculatedLipoma) - Patel, Saurabh; Sharma, Rajesh Kumar; Patel, Vaibhavi (Asian Journal of Pharmaceutical Research and Development, 2021)
A Lipoma is benign tumor made of fat tissue as per modern that resemble in Ayurveda as Granthi in general and medojagranthi as specific.In ayurvedic classic charaka and Sushruta mentioned the management of medojagranthi is the sakoshensastrendagdhvai.e total excision. In this case a 55 years old female patient visited OPD of Shalya tantra with complaints of hanging painless mass like swelling at right gluteal region. On the basis of clinical findings and USG report a lipoma was diagnosed and excision was done under local anaesthesia (2% lignocaine hydrochloride with adrenaline). After excision there was 60*54*24 mm size pedunculated lipoma noted. Hence this case highlighted that lipoma can occur at unusal place like gluteal region and need the excision.